Three new species in the subfamily Eriopeltinae Šulc from Italy (Hemiptera, Coccoidea, Coccidae) with comments on the genus Lecanopsis - Pellizzari, Giuseppina (Zootaxa, 2013)
Three new coccid species, namely Hadzibejliaspis ferenci Pellizzari n. sp., Lecanopsis sicula Pellizzari n. sp. and L. salvatorei Pellizzari n. sp. are described and illustrated. Identification keys for the genera in the subfamily Eriopeltinae Šulc and to species in the genera Hadzibejliaspis Koteja and Lecanopsis Targioni Tozzetti are provided.